Immune Dysfunction-Associated Elevated RDW, APACHE-II, and SOFA Scores Were a Possible Cause of 28-Day Mortality in Sepsis Patients - Wang J; He L; Jin Z; Lu G; Yu S; Hu L; Fang M; Jin X (Infection and Drug Resistance, 2024)
Jing Wang,1,* Lisha He,2,* Zhiyan Jin,1,* Guoguang Lu,1 Sufei Yu,1 Lingling Hu,1 Meidan Fang,1 Xiaxia Jin1 1Department of Clinical Laboratory, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Taizhou, Zhejiang Province, People’s Republic of China; 2Department of Ultrasound, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Taizhou, Zhejiang Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meidan Fang; Xiaxia Jin, Department of Clinical Laboratory, Taizhou Hospital of Zhejiang Province Affiliated to Wenzhou Medical University, Linhai, Taizhou, Zhejiang Province, People’s Republic of China, Tel +86 13586102337; +86 15967063239, Email fangmd@enzemed.com; jinxiax@enzemed.comObjective: To explore the early predictors and their predicting value of 28-day mortality in sepsis patients and to investigate the possible causes of death.Methods: 127 sepsis patients were included, including 79 cases in the survival group and 48 cases in the death group. The results of all patients on admission were recorded. After screening the risk factors of 28-day mortality, the receiver operating characteristic curve (ROC) was used to determine their predictive value for the 28-day mortality rate on admission, and the Kaplan-Meier curve was drawn to compare the 28-day mortality rate between groups. Finally, patients with cytokine and lymphocyte subsets results were included for investigating the possible causes of death through correlation analysis.Results: APACHE II (acute physiology and chronic health evaluation II), SOFA (Sequential Organ Failure Assessment) and red blood cell distribution width (RDW) were the risk factors for 28-day mortality in sepsis patients (OR: 1.130 vs.1.160 vs.1.530, P < 0.05). The area under the curve (AUC), sensitivity and specificity of APACHE II, SOFA and RDW in predicting the mortality rate at 28 days after admission in sepsis patients were 0.763 vs 0.806 vs 0.723, 79.2% vs 68.8% vs 75.0%, 65.8% vs 89.9% vs 68.4%. The combined predicted AUC was 0.873, the sensitivity was 89.6%, and the specificity was 82.3%. The Kaplan-Meier survival curve showed that the 28-day mortality rates of sepsis patients with APACHE II≥ 18.5, SOFA≥ 11.5 and RDW≥ 13.8 were 58.5%, 80.5% and 59.0%, respectively. In the death group, APACHE II was positively correlated with SOFA, IL-2, and IL-10, and RDW was positively correlated with PLT, TNF-α, CD3+ lymphocyte count, and CD8+ lymphocyte count.Conclusion: Sepsis patients with high APACHE II, SOFA and RDW levels at admission have an increased 28-day mortality rate. The elevation of these indicators in dead patients are related to immune dysfunction.Keywords: sepsis, APACHE II, SOFA, red blood cell distribution width, mortality, immune dysfunction